Application of the Principle of Delimitation Contradictions in Sporadic Land Registration in Bodeh District, Pemalang Regency: Penerapan Asas Kontradiktur Delimitasi dalam Pendaftaran Tanah Sporadik di Kecamatan Bodeh Kabupaten Pemalang - Qoyum Maulana (Unnes Law Journal, 2012)
Sporadic land registration is the registration of land for the first time where activities are held in actual measurement and mapping of land boundaries. This study aims to analyze the application, and the constraints faced by the application of the principle of delimitation contradictur in sporadic land registration in the District Bodeh District Immigration Office, as well as the actions of the District Land Office Pemalang if the principle has not yet been implemented. The data used are the primary and secondary. Juridical approach using empirical analysis. These results indicate that in the activities measurement and mapping of the boundaries of the land that there is a Principle of contradictur Delimitation and demarcation of the witnessed approval of the owners of land directly adjacent to the land to be registered. But in practice is still common disputes between landowners who will be registered with the adjacent landowners, including the dispute still exists the determination of the boundaries of the land is not witnessed by the owner of the land that borders the land to be registered. It is also happen in the District Bodeh Pemalang on sporadic land registration in 2009.